Environmental Accounting Practices of Selected Manufacturing Enterprises (Journal of Pharmaceutical Negative Results, 2022)
The study aims to inquiry about the current status of Environmental accounting practices (EAP) in manufacturing organizations inChittagong, Bangladesh. 16 manufacturing organizations have been chosen as a sample and revealed that 81.25% of sample enterprises useenvironmental accounting information anyhow. Ten structured questions on 7 points by polar Likert scale have included for considering theperception on EAP and got the average score 2.5124 on the scale of 3 which is highly appreciable. That is, respondents have shown a verypositive attitude regarding EAP. The study recommends Specific principles for Environmental reporting, Social policies for customer health,and introducing tax benefits for keeping pollution-free environment.